Towards a new generation of agricultural system data, models and knowledge products: Design and improvement - Antle, J; Basso, B; Conant, R; Godfray, H; Jones, J; Herrero, M; Howitt, R; Keating, B; Munoz-Carpena, R; Rosenzweig, C; Tittonell, P; Wheeler, T (Elsevier, 2016)
This paper presents ideas for a new generation of agricultural system models that could meet the needs of a growing community of end-users exemplified by a set of Use Cases.We envision new data, models and knowledge products that could accelerate the innovation process that is needed to achieve the goal of achieving sustainable local, regional and global food security. We identify desirable features for models, and describe some of the potential advances that we envisage for model components and their integration. We propose an implementation strategy that would link a “pre-competitive” space for model development to a “competitive space” for knowledge product development and through private-public partnerships for newdata infrastructure. Specific model improvements would be based on further testing and evaluation of existing models, the development and testing of modular model components and integration, and linkages of model integration platforms to new data management and visualization tools.